2018
DOI: 10.32861/jssr.spi5.916.925
|View full text |Cite
|
Sign up to set email alerts
|

Board of Directors and Environmental Reporting: Evidence From Plantation Industry.

Abstract: The purpose of this study is to examine the extent of environmental reporting by listed firms in the plantation industry in Malaysia. The relationship between board characteristics and the extent of environmental reporting by listed firms in Malaysia plantation industry is examined for the first three years after the issuance of the new revised Malaysian Code of Corporate Governance in 2012 (MCCG 2012). Three board characteristics have been used to explain the level of environmental reporting by Malaysia’s pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…Despite the minor decrease, Malaysian regulators can be optimistic as most companies have embraced the proposition by the MCCG to separate the chairman and CEO roles. The results are also consistent with prior reports and studies (Siman et al, 2018;Yusoff & Alhaji, 2012).…”
Section: Descriptive Analysissupporting
confidence: 93%
See 1 more Smart Citation
“…Despite the minor decrease, Malaysian regulators can be optimistic as most companies have embraced the proposition by the MCCG to separate the chairman and CEO roles. The results are also consistent with prior reports and studies (Siman et al, 2018;Yusoff & Alhaji, 2012).…”
Section: Descriptive Analysissupporting
confidence: 93%
“…Meanwhile, Siman, Ismail, Aziz, and Zam (2018) discovered that CEO duality does not influence firms' corporate decisions implying that CEO duality is detrimental to effective monitoring and independence of the board of directors. The result is similar to the studies by Mustapa, Ghazali, and Mohamad (2015) and Yusoff, Ahman, and Darus (2019) which concluded that the separation of the CEO and chairman could be more significant in describing firm performance.…”
Section: Ceo Duality and Firm Performancementioning
confidence: 99%
“…The palm oil plantations and mills in this country have undergone significant development and perhaps have a greater adverse impact on the environment. For example, in Sarawak, the increasing trend of newly planted areas has increased air, water and land pollution (Siman, Ismail, Aziz & Mohd Zam, 2018). 2 This situation arguably creates intense pressure on the plantation companies to be more socially and environmentally responsible.…”
Section: Introductionmentioning
confidence: 99%